Recent Advances in the Transcriptional Regulation of Secondary Cell Wall Biosynthesis in the Woody Plants - Zhang, Jin; Xie, Meng; Tuskan, Gerald A.; Muchero, Wellington; Chen, Jin-Gui (Frontiers in Plant Science, 2018)
Plant cell walls provide structural support for growth and serve as a barrier for pathogen attack. Plant cell walls are also a source of renewable biomass for conversion to biofuels and bioproducts. Understanding plant cell wall biosynthesis and its regulation is of critical importance for the genetic modification of plant feedstocks for cost-effective biofuels and bioproducts conversion and production. Great progress has been made in identifying enzymes involved in plant cell wall biosynthesis, and in Arabidopsis it is generally recognized that the regulation of genes encoding these enzymes is under a transcriptional regulatory network with coherent feedforward and feedback loops. However, less is known about the transcriptional regulation of plant secondary cell wall biosynthesis in woody species despite of its high relevance to biofuels and bioproducts conversion and production. In this article, we synthesize recent progress on the transcriptional regulation of secondary cell wall biosynthesis in Arabidopsis and contrast to what is known in woody species. Furthermore, we evaluate progress in related emerging regulatory machineries targeting transcription factors in this complex regulatory network of secondary cell wall biosynthesis.